MODELS OF COMMUNITY CAPACITY BUILDING FOR HOMESTAY MANAGEMENT - Ilham Junaid (Universitas Pendidikan Ganesha, 2021)
Tourists' visits to rural areas are increasingly experiencing growth. However, the community has not taken advantage of tourism as an opportunity to increase income. The research aims to identify the factors driving and inhibiting homestay management by the community, analyze the community's capacities and opportunities for homestay management, and propose a community capacity-building model for homestay management. This research employs a qualitative approach through a case study in Maen Village, Likupang, North Minahasa Regency. The research was carried out in 2020 through two periods of visits with interviews with residents and observation. The research reveals that the community had not yet optimized their house as a homestay. Residents' houses only serve as lodging for mining workers. However, residents do not mind providing their house as an accommodation based on homestay management principles. The strategic location of Maen Village, the hospitality of the residents, and the use of people's houses as lodging are the driving forces for homestay management. A weak understanding of homestay is a challenge for most residents. Community capacity still needs to be improved with various training programs. This study proposes two homestay management models and development, including, entrepreneurial-based community capacity model and a homestay management model based on digital marketing principles. This research validates the concept of community capacity through homestay management. In addition, the paper provides an insight on how to utilize the opportunities possessed by the local community to obtain alternative income through homestay management.